Characterization of Pustular Mats and Related Rivularia-Rich Laminations in Oncoids From the Laguna Negra Lake (Argentina) - Mlewski, Estela C.; Pisapia, Céline; Gomez, Fernando; Lecourt, Lena; Soto Rueda, Eliana; Benzerara, Karim; Ménez, Bénédicte; Borensztajn, Stephan; Jamme, Frédéric; Réfrégiers, Matthieu; Gérard, Emmanuelle (Frontiers in Microbiology, 2018)
Stromatolites are organo-sedimentary structures that represent some of the oldest records of the early biosphere on Earth. Cyanobacteria are considered as a main component of the microbial mats that are supposed to produce stromatolite-like structures. Understanding the role of cyanobacteria and associated microorganisms on the mineralization processes is critical to better understand what can be preserved in the laminated structure of stromatolites. Laguna Negra (Catamarca, Argentina), a high-altitude hypersaline lake where stromatolites are currently formed, is considered as an analogue environment of early Earth. This study aimed at characterizing carbonate precipitation within microbial mats and associated oncoids in Laguna Negra. In particular, we focused on carbonated black pustular mats. By combining Confocal Laser Scanning Microscopy, Scanning Electron Microscopy, Laser Microdissection and Whole Genome Amplification, Cloning and Sanger sequencing, and Focused Ion Beam milling for Transmission Electron Microscopy, we showed that carbonate precipitation did not directly initiate on the sheaths of cyanobacterial Rivularia, which dominate in the mat. It occurred via organo-mineralization processes within a large EPS matrix excreted by the diverse microbial consortium associated with Rivularia where diatoms and anoxygenic phototrophic bacteria were particularly abundant. By structuring a large microbial consortium, Rivularia should then favor the formation of organic-rich laminations of carbonates that can be preserved in stromatolites. By using Fourier Transform Infrared spectroscopy and Synchrotron-based deep UV fluorescence imaging, we compared laminations rich in structures resembling Rivularia to putatively chemically-precipitated laminations in oncoids associated with the mats. We showed that they presented a different mineralogy jointly with a higher content in organic remnants, hence providing some criteria of biogenicity to be searched for in the fossil record.